Challenges of Seasonal Green Vegetable Marketing in Nepal: A Study of Chitwan District - Dhakal, Chandra Prasad (NPRC Journal of Multidisciplinary Research, 2025)
This study examines the challenges of seasonal green vegetable marketing in Nepal, with a focus on Chitwan district, assessing the status of farming and key obstacles in the marketing of produce such as cauliflowers, cabbage, tomatoes, pumpkins, and leafy greens. Using a mixed-method research design, the study combines qualitative and quantitative approaches, analyzing data from 50 respondents, including farmers, businesspersons, local leaders, and government agriculture staff. The findings reveal major challenges such as a traditional and inefficient marketing system, lack of market information and price transparency, insufficient storage facilities, black marketing, monopolistic practices, and high production costs. The study concludes that improving market infrastructure, enhancing price dissemination mechanisms, expanding storage facilities, and regulating unfair trade practices are essential for addressing these issues. Based on primary data, the research provides actionable insights for policymakers and stakeholders to strengthen Nepal’s agricultural marketing system.